Representasi Feminisme Radikal dalam K-Drama sebagai Resistensi Budaya Patriarki - Novianty, Suci Marini (Magister of Communication Science, Sahid University Jakarta., 2024)
This study examines the representation of radical feminism in the South Korean drama